A CRITICAL DISCOURSE ANALYSIS OF DONALD J. TRUMP’S SPEECH ON US PRIME TIME ABOUT CORONAVIRUS IN AMERICA - Dian Purnama Sari; Latifah Amaliny (International Conference on Social and Islamic Studies, 2021)
This research critically examines the speech delivered by the American former President, Donald Trump in 2020 about coronavirus in America. The researcher has taken the data from YouTube that belongs to CNBC Television which was broadcasted live from the White House on March 11, 2020. It was found a relationship between language, power, and ideology based on the speech delivered. Therefore Critical Discourse Analysis is conducted to reveal the concepts and hidden ideologies implied in Trump‘s speech. There are three problems to be solved, namely:  the social wrong, the obstacles to addressing the social wrong, and social order needs the social wrong in Donald J Trump‘s speech. This study used a qualitative approach and three-dimension of CDA by Norman Fairclough. The result shows that there are three social wrongs in Donald Trump‘s speech; Trump‘s instability in evaluating coronavirus seriousness, Trump‘s self-positive evaluation to his government and negative evaluation to others, and COVID ―hate crimes‖ against Asian and non-originally Americans. The obstacle to social wrongs being tackled are the coronavirus outbreak in America and other countries' inability to stop the virus, time of election campaign, and Trump misinformation in delivering his speech.